HUBUNGAN BEBAN KERJA PERAWAT DENGAN KEPATUHAN MENCUCI TANGAN DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Farikha Annisa Dewi; Yuni Kurniasih; Rohayati Masyitoh (Jurnal Kesehatan, 2025)
Background: Workload that greatly affects the level of motivation to the productivity of a worker. Excessive workload can cause problems in the workplace, especially in washing hands. Washing hands in a nurse is the main requirement that must be met before and after performing patient actions. Objective: To determine whether there is a relationship between nurses' workload and hand washing compliance at PKU Muhammadiyah Hospital Yogyakarta. Method: This study uses quantitative research and uses a descriptive correlative design with a cross-sectional method. The research instrument was a nurse's workload questionnaire and used a hand washing compliance observation sheet. Data analysis used the Chi-square test. Results: From 68 respondents, Based on the analysis results, it was found that the nurses' workload showed a moderate majority of 36 respondents (52.9%). Meanwhile, the results of the hand washing compliance analysis showed that the majority of nurses at PKU Muhammadiyah Hospital Yogyakarta were compliant with the results of 35 respondents (51.5%). The results of the Chi- Square test showed a p value = 0.000, which means that there is a significant relationship between nurses' workload and hand washing compliance. Conclusion: Nurses' workload if the category is moderate-high greatly affects hand washing compliance.